2015
DOI: 10.1007/s10916-015-0235-1
|View full text |Cite
|
Sign up to set email alerts
|

A Security Framework for Nationwide Health Information Exchange based on Telehealth Strategy

Abstract: This study focuses on the situation of health information exchange (HIE) in the context of a nationwide network. It aims to create a security framework that can be implemented to ensure the safe transmission of health information across the boundaries of care providers in Malaysia and other countries. First, a critique of the major elements of nationwide health information networks is presented from the perspective of security, along with such topics as the importance of HIE, issues, and main approaches. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…Time spent by the hospital staff in verifying information could be reduced, which includes that of medical tests, results and diagnoses of patients (Blaya et al, 2010;Payne et al, 2011;Zaidan et al, 2015;Williams et al, 2016). Zaidan et al (2015) also found that the costs could be reduced by using HIE; for example, reducing the duplication of tests and results as well as less usage of paper in hospitals (Yaraghi, 2015;Zaidan et al, 2015;Bailey et al, 2013;Miller & Tucker, 2014).…”
Section: Benefits Of Hospital Information Exchangementioning
confidence: 97%
See 4 more Smart Citations
“…Time spent by the hospital staff in verifying information could be reduced, which includes that of medical tests, results and diagnoses of patients (Blaya et al, 2010;Payne et al, 2011;Zaidan et al, 2015;Williams et al, 2016). Zaidan et al (2015) also found that the costs could be reduced by using HIE; for example, reducing the duplication of tests and results as well as less usage of paper in hospitals (Yaraghi, 2015;Zaidan et al, 2015;Bailey et al, 2013;Miller & Tucker, 2014).…”
Section: Benefits Of Hospital Information Exchangementioning
confidence: 97%
“…According to Zaidan et al (2015), healthcare is safer by using HIE. This is because security errors of patients could be reduced by using HIE as declared by Kaelber & Bates (2007 ).…”
Section: Benefits Of Hospital Information Exchangementioning
confidence: 99%
See 3 more Smart Citations